Ketamine in the treatment of cocaine use disorders - Pereira, Ronaldo Cascelli Schelb Scalla; Henriques, Bruno David; Amaro, Marilane de Oliveira Fani; Moreira, Tiago Ricardo; Rosa, Marcelo Barcellos da; Pereira, Valdinei Godinho; Junqueira, Leonardo de Paula; Oliveira, Thaila Vidal de; Cascelli, João Eduardo Schelb Scalla Pere; Pereira, Davi Cascelli Schelb Scalla; Parreiras, Emanuelle Emília Ferreira; Carvalho, Camilo Amaro de (Ciência e Natura, 2022)
Introduction: ketamine is a dissociative anesthetic and, recently, its antidepressant properties has been described. Besides, its safety has been proven in the treatment of Stimulant Use Disorders. Objective: to evaluate the use of ketamine in the treatment of Stimulant Use Disorders (specially cocaine and its byproducts). Methods: patient’s motivation for change was measured by URICA scale and psychiatric symptoms by EAS-40 score, both before and after the intervention. Results: it was verified, after the comparison between the Readiness Score means, an increase in the motivation for change after ketamine’s single administration, when compared to the moments before and after the intervention. Analyzing the Global Severity Index before and after ketamine administration, by EAS-40 score, we noticed a slight reduction of the psychiatric symptoms before and after the intervention. Conclusion: it was proven that ketamine’s single administration led to a quick and lasting improvement on the user’s motivation without worsening the mental health status.